Modern software engineering methodologies for mobile and cloud environments - Cruz, Antonio Miguel Rosado da, 1970-; Paiva, Sara, 1979- (Advances in systems analysis, software engineering, and high performance computing (ASASEHPC) book series., 2016)
"This book investigates emergent trends and research on innovative software platforms in mobile and cloud computing, featuring state-of-the-art software engineering methods, as well as new techniques being utilized in the field"- Resumé vydavatele